Application of Magnetically Controlled Sorbents for Detoxication - Butusova, O.A. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This work shows the conditions that ensure the efficiency of the device for extracorporeal detoxification using new technologies using magnetically controlled sorbents. The above technique allows calculating and, accordingly, optimizing the parameters of one of the important components of this device - the unit for sorption and removal of toxins from biofluid. A weighted estimate of the required concentration of magnetically controlled sorbents in the biofluid being purified, the amount and concentration of an emulsion containing a magnetically controlled sorbent, and the duration of the procedure ensures the safety and effectiveness of this method of medical care.